Advancing flood resilience: the nexus between flood risk management, green infrastructure, and resilience - Takin, Mehrafarin; Cilliers, Elizelle Juanee'; Ghosh, Sumita (Frontiers in Sustainable Cities, 2023)
Climate change and the fast pace of urbanisation are two major factors contributing to the exacerbated risk of flooding in urban areas. Flood resilience strategies, underpinned by the principles of green infrastructure, are gaining importance as within broader spatial planning approaches, and various global cities are adopting revised policies and frameworks to improve flood risk management. Yet, such responsive approaches are still limited and context-specific. This paper reflects on the concepts of flood risk management, flood resilience and green infrastructure planning to identify the synergies between these concepts, and identify challenges that are prohibiting global flood resilience. The paper also draws planning recommendations for advancing flood resilience through governance and an integrated planning approach, in support of the global goals towards flood resilience.